Synthesis of Au/Al2O3 nanocatalyst and its application in the reduction of p-Nitrophenol - Yazid, Hanani; Adnan, Rohana; Farrukh, Muhammad Akhyar; Abd Hamid, Shafida (Chung-Kuo Hua Hsueh Hui, 2011)
Gold (Au) nanoparticles supported on alumina (Al2O3) were prepared at several pH levels via the deposition- precipitation (DP) method. The effects of pH at below and above the isoelectric point (IEP) of Al2O3 as well as the pH adjustment before and after the addition of the support into the gold chloride solution were investigated. The results revealed the formation of cationic, clusters andmetallic Au on alumina. The catalytic activity of these species was tested in the reduction of p-nitrophenol (p-NP) using hydrazine as a reductant. The catalytic reaction was monitored spectrophotometerically and the highest rate constant (k) achieved based on pseudo first order kineticmodel was 12.7 10-3 s-1. Structural and elemental characterizations of the supported gold nanoparticles were carried out using X-ray diffraction (XRD), transmission electronmicroscopy (TEM), scanning electronmicroscopy (SEM), energy-dispersive X-rays (EDX), atomic absorption spectrometry (AAS), and ultraviolet-visible spectroscopy (UV-Vis).